2014
DOI: 10.1371/journal.pone.0098529
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting the Post-Transplantation Growth and Survivorship of Juvenile Scleractinian Corals via Nutritional Enhancement

Abstract: Size-dependant mortality influences the recolonization success of juvenile corals transplanted for reef restoration and assisting juvenile corals attain a refuge size would thus improve post-transplantation survivorship. To explore colony size augmentation strategies, recruits of the scleractinian coral Pocillopora damicornis were fed with live Artemia salina nauplii twice a week for 24 weeks in an ex situ coral nursery. Fed recruits grew significantly faster than unfed ones, with corals in the 3600, 1800, 600… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 38 publications
(70 reference statements)
1
35
0
Order By: Relevance
“…Cost-benefit analyses also represent a useful tool for monetising strategies so that reef restoration can be carried out more effectively at lower cost (Edwards et al, 2010b). Toh et al (2014) showed that while labour and equipment contributed significantly to the cost of producing sexually propagated corals for transplantation, greater economies of scale could be achieved by introducing feeds to augment coral growth during the nursery phase. Additionally, factors such as the evolutionary distinctiveness or vulnerability of a species to global extinction can be considered when prioritising corals for restoration (Curnick et al, 2015;Huang and Roy, 2015), to supplement broad-based proxies such as site-specific species rarity.…”
Section: Incorporation Of Novel Techniques Into Restoration Designmentioning
confidence: 99%
“…Cost-benefit analyses also represent a useful tool for monetising strategies so that reef restoration can be carried out more effectively at lower cost (Edwards et al, 2010b). Toh et al (2014) showed that while labour and equipment contributed significantly to the cost of producing sexually propagated corals for transplantation, greater economies of scale could be achieved by introducing feeds to augment coral growth during the nursery phase. Additionally, factors such as the evolutionary distinctiveness or vulnerability of a species to global extinction can be considered when prioritising corals for restoration (Curnick et al, 2015;Huang and Roy, 2015), to supplement broad-based proxies such as site-specific species rarity.…”
Section: Incorporation Of Novel Techniques Into Restoration Designmentioning
confidence: 99%
“…nauplii show optimal growth and survival in home aquaria (Van Os et al 2012). Invertebrate feeding, such as corals, is highly improved if live food can be used (Toh et al 2014). It seems that this sector is dominated by aquafeed companies information more than by scientific information (Forsman et al 2012).…”
Section: Zooanthropological Considerations About Ornamental Fish Feedsmentioning
confidence: 99%
“…; Monticini ; Toh et al . ). Therefore, several studies are focussed on modern aquaculture methods for improving ornamental farming (Pomeroy et al .…”
Section: Introduction To Artificial Feeding In Ornamental Aquaculturementioning
confidence: 97%
See 1 more Smart Citation
“…While there has been significant progress in rearing techniques, such as introducing nutritious feeds and increasing bicarbonate ions to enhance coral growth rates (Forsman, Page, Toonen, & Vaughan, 2015;Lirman et al, 2014;Marubini & Thake, 1999;Toh, Ng, Peh, Toh, & Chou, 2014), it is also essential that the enhanced productivity is documented by precise measurements. In coral mariculture, various methods exist to determine growth rates.…”
mentioning
confidence: 99%